-2a-9=6x+15

Simple and best practice solution for -2a-9=6x+15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2a-9=6x+15 equation:


Simplifying
-2a + -9 = 6x + 15

Reorder the terms:
-9 + -2a = 6x + 15

Reorder the terms:
-9 + -2a = 15 + 6x

Solving
-9 + -2a = 15 + 6x

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '9' to each side of the equation.
-9 + 9 + -2a = 15 + 9 + 6x

Combine like terms: -9 + 9 = 0
0 + -2a = 15 + 9 + 6x
-2a = 15 + 9 + 6x

Combine like terms: 15 + 9 = 24
-2a = 24 + 6x

Divide each side by '-2'.
a = -12 + -3x

Simplifying
a = -12 + -3x

See similar equations:

| -3x-45=-11x+51 | | f(x)=-12x+48 | | .3x-2.3=.1 | | 2(4y-3)=-10 | | -7w+2(w+4)=3 | | 8+x=-21 | | -32+t+18= | | 5y+12=57 | | 12=x^2-4 | | 10x+y=7(x+y) | | -25+2v=-56v-42 | | 50c+5f+10cr+fr=0 | | r^2-r+2=7 | | X+5+3x+5=180 | | y+3=-.5(x+5) | | 7b=6b-9 | | -5(2t-2)+6t=5t-6 | | (-19)+x=-33 | | 40=2y+12 | | 0.04(y-7)+0.12y=0.20y-.6 | | 36x^3-15x=0 | | Ax+5=bs-c | | k-4-6=-16 | | 3y-1=x+5 | | 3x^6+6x^4-24x^5=0 | | 5(2x-1)+4x+2=11 | | x-126=35+8x | | -4=x+-7 | | Y=-16x^2+16x+5 | | Ax+5=bc-c | | x=9x+5-5 | | 6n+4=-2n |

Equations solver categories